Engajamento público: uma análise na perspectiva de múltiplos stakeholders - Rodrigues, Sâmila de Sousa (2024)
This research investigated the following question: How can electronic government be used to engage stakeholders in decision-making processes? With this intention, the context chosen was the Participatory Budget - PB - policy of Teresina, at the municipal and state level. The general objective was to analyze how electronic government can be used to engage stakeholders in decision-making processes, taking into account contexts, stakeholder groups and technological tools. To achieve this, a qualitative data approach was adopted as a research method, with semistructured interviews carried out with stakeholders of PB programs. The research result presented, from the stakeholders' perspective, the factors that influence stakeholders participation, as well as the electronic government tools that can be used for engagement. Furthermore, the results revealed democratic limitations in the municipal PB, with involvement restricted to community entities, while the state PB program demonstrated more ample participation, especially through the effective use of electronic tools. That way, this research fills a gap by considering the perspective of stakeholders in the analysis of stakeholders engagement through electronic government. It also stands out as a pioneer in perceiving the state program as a suitable research environment to evaluate the effectiveness of implementing electronic government as a means of engaging stakeholders in decision-making processes. The research also contributes to public management, since managers are responsible for adopting behaviors and making decisions that encourage stakeholders engagement. Finally, this study offers practical guidance for Participatory Budget programs and similar contexts, highlighting the relevance of electronic government in increasing engagement and transparency in decisionmaking processes.